Viscometer for measuring viscosity of thixotropic fluids; AIP Conference Proceedings; Vol. 2310, iss. 1 : Physical Mesomechanics. Materials with Multilevel Hierarchical Structure and Intelligent Manufacturing Technology - Bogoslovsky A. V.; Kozhevnikov I. S.; Galkin V. M. Vladislav Mikhailovich; Altunina L. K. (2020, 2020)
Title screen